Associativity and brand management: need to enter new markets - Haku Wiñay Project : Associativity and brand management: need to enter new markets - Haku Wiñay Project – Tacna - Wong Copaja, Edgard Enrique (2021)
Today, we begin to reflect on one of the strategies to confront poverty and extreme poverty that has stood out in Peru. Peruvian entrepreneurs are characterized by ingenuity, creativity and are always ready to find solutions in unfavorable financial contexts. In fact, about half of the country's business is driven by economic need. Given this, it is necessary to raise a good idea and develop a plan to turn it into a business opportunity. This is how the Haku Wiñay project begins to carve, since it is a project that aims to develop the productive capacity and entrepreneurship of poor and extremely poor families living in densely populated areas in order to increase and diversify independent income. sustainable.